2009
DOI: 10.1111/j.1365-2702.2008.02477.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient participation in emergency care – a phenomenographic analysis of caregivers’ conceptions

Abstract: Mutual participation is perceived occasionally and often unexpectedly, when the right circumstances occur, despite international and national guidelines that lay down the need for patient participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 25 publications
3
41
0
4
Order By: Relevance
“…Some of the requisites for and constraints to patient participation identified in this study have previously been reported in nursing literature [20,21,23,25]. Despite differences in patient populations, settings, and professionals, there seem to be similarities about important requisites for patient participation.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Some of the requisites for and constraints to patient participation identified in this study have previously been reported in nursing literature [20,21,23,25]. Despite differences in patient populations, settings, and professionals, there seem to be similarities about important requisites for patient participation.…”
Section: Discussionmentioning
confidence: 51%
“…However, some persons with SCI quickly understand what has happened to them and the consequences of their injury, whereas others require much more time to fully appreciate the trauma and to become receptive to new information [33,41]. In line with findings from some nursing studies [23,25], our informants stated that in the initial phase full patient participation could be difficult to achieve because of the patient's inability to grasp information. This necessitates that the information should be clearly stated and repeated.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Professionals' abilities and willingness to facilitate patient participation were seen as a general problem (Frank et al, 2009a;Fig. 1.…”
Section: The Patient-nurse Relationship -Professional Dominance Restrmentioning
confidence: 99%
“…Consistent with other studies (Frank et al 2008;Lemonidou et al 2003), information was regarded as a prerequisite for patient participation and patient autonomy. Even if ICU-patients often hand themselves over to the care professional, the CP was conceived of as contributing to uniform information and thereby facilitating patient participation, a finding consistent with other studies (Barker et al 1999;Currie and Harvey, 2000;De Luc, 2000).…”
Section: Holistic Carementioning
confidence: 61%